ChemInform Abstract: Universal Approach to the Synthesis of Silver Sulfide in the Forms of Nanopowders, Quantum Dots, Core‐Shell Nanoparticles, and Heteronanostructures. Issue 51 (5th December 2016) - Sadovnikov, Stanislav I.; Gusev, Aleksandr I.
Abstract: Review: [70 refs.